PENERAPAN MODEL CTL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 001 BUKIT KAPUR - Wahyudi, Kamal Wahyudi; Witri, Gustimal Witri; Marhadi, Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem in this study is the low third grade math learning outcomes. Lays flat - initial average score of 63.4. This study aims to improve outcomes Mathematics Elementary School third-grade students through the Chalk Hill 001 "Application of Models of Contextual Teaching And Learning (CTL)". Instrument of data collection in this thesis is a test of student learning outcomes, teacher observation sheet activities and observation of student activity sheets. This study was conducted in March 2014 conducted by 2 siklus.Subyek this study were students of class III Elementary School 001 Bukit Kapur totaling 28 students. Teacher activity cycle I first encounter with the percentage of 56.26% with enough categories, increased in the first cycle II meeting with the percentage of 62.50% categorized good, then an increase in the second cycle first meeting with the percentage of 68.75% categorized very well, and the second cycle of the second meeting with the percentage of 87.50% categorized very well. While the activities of students in the first cycle the first meeting with the percentage of 56.26% to the category of fairly elevated in the first cycle of the second meeting of the percentage of 62.50% with a good category. In the second cycle the first meeting with the percentage of 68.75% amamt both categories have increased in the second cycle II meeting with the percentage of 87.50% categorized very well. Average - average learning outcomes increased from baseline score. Value - average score of 64.3 basis increased in the first cycle with value - average 76.43 and the second cycle increased to 86.43. Percentage increase in learning outcomes of basic scores to UH I reached 24.42% and from the base to the UH II scores increased by 40.70%, the percentage reached 89.29% completeness and otherwise completed. From these results it can be concluded that the application of Model Contextual Teaching And Learning (CTL) to Improve Student Learning Outcomes Math Class III Elementary School 001 Bukit Kapur. Keywords: Teaching And Learning Model Contextuak Learning (CTL). Results Beleajar Math.